Reflections on Attention-deficit and Disruptive Behavior Disorders - W. Ver Eecke (Current Innovations in Disease and Health Research Vol. 7, 2023)
ADHD is a neurodevelopmental disease marked by excessive quantities of impulsivity, hyperactivity, and inattention that are pervasive, problematic in a variety of circumstances, and generally age-inappropriate. Under the umbrella of attention-deficit and disruptive behavior disorders, the authors of the DSM-IV-TR group four disorders (DSM IV, pp. 85–103). "Disruptive behavior disorder not otherwise specified" (Ibid., p. 93) is the fourth group. Thus, the following three options are left: 1) Attention-deficit/hyperactive disorder. 2) Conduct disorder. 3) Oppositional defiant disorder. The diagnostic criteria for ADHD, conduct disorder, and oppositional defiant disorder all include a number of factors pertaining to disobedience to authority. In this article, I will ask if there could be any objective reasons why the children affected by these disorders are compelled or encouraged to avoid or to oppose rules. A more positive way of approaching the problem is to ask if following rules could be made easier or made more meaningful. If so, then it would be possible to formulate helpful approaches to be used by adults having to deal with children affected by those disorders. These helpful approaches could then be used by parents, by therapeutic professionals, and by educators.